Regulatory Immune Cells in Idiopathic Pulmonary Fibrosis: Friends or Foes? - van Geffen, Chiel; Deißler, Astrid; Quante, Markus; Renz, Harald; Hartl, Dominik; Kolahian, Saeed (Frontiers in Immunology, 2021)
The immune system is receiving increasing attention for interstitial lung diseases, as knowledge on its role in fibrosis development and response to therapies is expanding. Uncontrolled immune responses and unbalanced injury-inflammation-repair processes drive the initiation and progression of idiopathic pulmonary fibrosis. The regulatory immune system plays important roles in controlling pathogenic immune responses, regulating inflammation and modulating the transition of inflammation to fibrosis. This review aims to summarize and critically discuss the current knowledge on the potential role of regulatory immune cells, including mesenchymal stromal/stem cells, regulatory T cells, regulatory B cells, macrophages, dendritic cells and myeloid-derived suppressor cells in idiopathic pulmonary fibrosis. Furthermore, we review the emerging role of regulatory immune cells in anti-fibrotic therapy and lung transplantation. A comprehensive understanding of the immune regulation could pave the way towards new therapeutic or preventive approaches in idiopathic pulmonary fibrosis.